Cubic-spinel AgIn5S8-based thermoelectric materials: synthesis, phonon transport and defect chemistry. (July 2022) - Zhang, Chaohua; Dou, Yubo; Chen, Jiali; Fang, Susu; Xu, Weigao; Wu, Xuelian; Hu, Lipeng; Liu, Fusheng; Li, Yu; Li, Junqin
Abstract: Cubic-spinel Ag1-x Cux In5 S8 is promising as it is a kind of In–S-based thermoelectric material using eco-friendly elements like In, Cu and S. Here, we develop a melting method to synthesize single-phase Ag1-x Cux In5 S8 alloys using metal sulfides as precursors, and we also comprehensively study their thermoelectric properties, chemical bonding, electronic and phonon structures, and defect chemistry. Owing to the complex crystal structures, weak chemical bonding, and "rattling-like" phonon modes, the Ag1-x Cux In5 S8 alloys show low lattice thermal conductivity of ∼0.63–0.72 Wm −1 K −1  at 873 K. The optimal figure of merit ( ZT ) of the n-type Ag1-x Cux In5 S8 can reach ∼0.31 at 873 K, which is higher than the theoretical prediction. The diamond-like crystal structures also enable them to have good mechanical properties, with a hardness of ∼3.95 GPa, comparable to those thermoelectric materials with the highest mechanical strength. Our understanding of the "rattling-like" phonon modes and defect chemistry in AgIn5 S8 can also guide the further development of the more promising p-type AgIn5 S8 and other advanced cubic-spinel thermoelectric materials. Graphical abstract: Image 1 Highlights: Cubic-spinel sulfide-type AgIn5 S8 -based alloys are synthesized. A hardness of ∼3.95 GPa can be achieved. The "rattling-like" phonon mode is proved for a low κ l a t . The defect chemistry for n-type doping behavior is revealed.